CONTROL OF MODULAR CONVEYOR AND AUTOMATED HANDLING DEVICES INTERCONNECTION - Vaclav Cempirek (Advances in Science and Technology Research Journal, 2018)
The paper focuses on modular conveyors, mainly dedicated for the transport of parcel goods of various properties. Accent will also be put to their use in processes where the belt's resistance to higher temperatures or to mechanical damage is required. The solution is aimed on the use for installation in larger transport units, production as well assembly lines. The proposal of the conveyor design allows to handle different line sections (bends, broken sections, etc.) using a single drive. The conveyor track will be solved with aim to the transport of goods (products) by means of automated trolleys. A proposal for the synchronization of the conveyor track with an automated handling device will be presented, which will ensure the final phase of the production chain, the relocation of production to the warehouse of finished products. The authors will focus on the calculation of subsequent intervals for automated means of handling as well on determining the capacity of the conveyor track.